Challenges of Higher Educational Documentary Institutions in Supporting Merdeka Belajar Kampus Merdeka Program - Ciwuk Musiana Yudhawasthi; Lydia Christiani (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
Independent Learning Independent Campus (MBKM) was launched by the Ministry of Education, Culture, and Research and Technology to support the readiness of students to face challenges in the world of work by applying active learning. Documentary institutions in universities, namely libraries, archives, and museums, should become strategic partners in supporting the MBKM program because the documentary institution has all the necessary conditions, facilities, and infrastructure to succeed MBKM program. This study aimed to determine the readiness of documentary institutions in the university environment to exploit the opportunities and challenges and what obstacles they encountered. This study used the qualitative method and in-depth interviews for data collection and a literature study. The researcher concludes that the biggest challenges facing documentary institutions are regulation and the readiness of human resources. Due to this, changes to regulations and educational curricula and the introduction of new documentation of pure science are priorities in improving professional education providers in library science, archives, and museology.